IN VITRO SHOOT REGENERATION AND PLANTLET DEVELOPMENT IN SAFFLOWER (CARTHAMUS TINCTORIUS L.) - NIKHIL, MOHITE; M. S. DUDHARE; P. V. JADHAV; M. P. MOHARIL; A. G. DESHMUKH (The Bioscan, 2014)
In vitro plant regeneration using cotyledonary leaf segments as explants was studied in two varities of safflower (Carthamus tinctorius L.) namely AKS-207 and PKV-pink. Best result of callusing in both varities was observed after 21days of culture initiation on medium supplemented with TDZ (2.0mg/L) + NAA (0.5mg/L). Maximum percentage of shoot initiation (63.33%) in AKS-207 was observed on a medium fortified with TDZ (2.0mg/L) + NAA (0.1mg/L). While in PKV-pink it was observed on a medium fortified with TDZ (2.0mg/L) + NAA (0.5mg/ L). Subsequent culturing of these responded explants resulted into maximum percentage of shoot multiplication on a medium fortified with TDZ (2.0mg/L) + NAA (0.1mg/L) for AKS-207 and TDZ (2.0mg/L) + NAA (0.5mg/ L) for PKV-pink. Proliferated and well developed shoots were then rooted in medium having different concentrations of NAA. Rooted shoots were successfully acclimatized and established in greenhouse.